Kinerja Pustakawan Di Era Transformasi Digital - Supriati, Eny (Pustakaloka, 2024)
This study aims to analyze the factors that influence the performance of librarians at the IAIN Ponorogo Library in facing the challenges of digital services and formulating strategies for improving them. The method is descriptive qualitative, with data collected through in-depth interviews, direct observation, and documentation. Interviews involved 3 librarians, 2 lecturers, and 5 students. The results show three main strategies to improve librarian performance: training and development, improving communication, and cooperation between librarians. Five factors influence the improvement of librarian performance: librarian knowledge and skills, management support, utilization of information technology, cooperation between librarians, and work motivation. With these strategies and supporting factors, libraries can improve the efficiency and quality of services provided to users, creating a better and more relevant library experience in the digital era. Keywords: employee performance; librarian; digital transformation; library services